Complex system of quality control of specialists’ training at HEI: project organization and functioning - Kolodii Ihor; Yastrubetska, Halyna I.; Kanibolotska Olha; Kubitskyi, Serhii; Kolomiiets, Tetiana (My University, 2021)
The article aims to form the special features of using pedagogical technologies of designing and functioning of the complex system of quality control of specialists' training in HEIs. The methodology of the article is built on the statistical analysis of the results of the OECD TALIS (2018) survey of HEIs teachers in the Czech Republic, which allow us to determine the pedagogical technologies of the functioning of a comprehensive system of quality control of training specialists in HEIs. The sample included 6,039 HEIs teachers, of whom 72.4% were women and 27.6% were men. The results show differences between the countries (the Czech Republic, Poland, and Hungary) in the level of innovativeness of HEIs teaching and the level of involvement of students in the development of innovations.
Keywords: Pedagogical technologies; Quality control of training; Quality control system; HEIS; Quality of specialists' training